The Past and Future of Psychedelic Science: An Introduction to This Issue. Issue 2 (15th March 2019) - Doblin, Richard E.; Christiansen, Merete; Jerome, Lisa; Burge, Brad
ABSTRACT: Psychedelic plants and fungi have been used in indigenous medicinal traditions for millennia. Modern psychedelic research began when Albert Hofmann first synthesized lysergic acid diethylamide (LSD-25) in 1938. Five years later, became the first person to ingest LSD. Hofmann was unaware of the significance of his actions, and the effects they would set in motion. After a burgeoning period of scientific and cultural exploration in the1950s and '60s, psychedelic research was slowed to a near halt. Throughout the 1970s and '80s governmental interventions severely hampered global psychedelic research, despite evidence of the limited medical risks and therapeutic potential of psychedelics. After decades of persistent education and advocacy, rigorous research employing psychedelics as tools of discovery and healing are abundant today. Studies are taking place in research institutions and in private practice sites supported by non-profit and for-profit organizations, as well as individual investigators. This research includes clinical trials with MDMA-assisted therapy for the treatment of PTSD, alcoholism, and social anxiety, and psilocybin clinical studies for depression and addiction, as well as the ability of psychedelics to catalyze spiritual or mystical experiences and inspire creativity, and into the neuroscientific understanding the effects of psychedelic substances on our nervous system.